Implications of climate change on human comfort in buildings: evidence from Nkontompo community of Sekondi-Takoradi, Ghana (Journal of Science and Technology, 2016)
Climate Change has become the most talked about issue in recent times. The impact of climate change is likely to become more evident in the coming decades. Currently, atmospheric conditions, especially in the dry season, are getting hotter and drier with increased heat waves. Increased demand for air conditioning for space cooling as a result of internal discomfort in buildings is already manifesting. This could put an additional stress on the already over-burdened energy capacity of the nation. The study on implications of climate change on human comfort in buildings was conducted in Nkontompo community, a suburb of Sekondi-Takoradi Metropolitan area of the Shama-Ahanta District of the Western Region of Ghana. The objectives of this study are to assemble and disseminate information about some of the possible impacts of climate change on the built environment. This is to set the platform for building professionals to identify possible adaptive measures to serve as basis for development of standards to maintain and enhance the quality of life in buildings. The results showed that there were significant changes in temperature, precipitation, and relative humidity. A rise in temperature and humidity levels constitutes a potential hazard to health and human comfort and accelerates many degradation processes and material damage. Subsequently, the amount of energy needed to maintain the condition of air in spaces at comfort levels keep increasing. It is therefore imperative that landlords and other property owners should be effectively guided by qualified professionals within the framework of policy guidelines based on sound research.